Pengaruh Kecerdasan Emosional, Iklim Organisasi dan Kepuasan Kerja Terhadap Kinerja Perawat di Rumah Sakit Umum Hermana Lembean - Veronica Christy Elisabeth Laoh; Barnabas Harold Ralph Kairupan; Jeini Ester Nelwan (STIKes Payung Negeri Pekanbaru, 2022)
Introduction: Nurse performance is the result of work in quality and quantity achieved by a nurse. Achievement of good performance or less influenced by certain factors, such as knowledge, motivation and self-confidence. It is also influenced by leadership, responsibility, discipline, initiative. The purpose of this study was to analyze the effect of emotional intelligence, organizational climate and job satisfaction on the performance of nurses at the Hermana Lembean General Hospital. Method: This research is a correlational study. This research was conducted at the Hermana Lembean General Hospital in January-February 2022. The research respondents were 123 nurses. The variables in this study are emotional intelligence, organizational climate, job satisfaction and nurse performance. The instrument used is a questionnaire. Multivariate data analysis using Structural Equation Modeling (SEM) with smartPLS. Results: The results showed that that the influence of organizational climate on performance obtained a p-value of 0.171 with a T statistic of 0.953 with a positive path coefficient of 0.093, which means that organizational climate has no significant effect on performance. The influence of emotional intelligence on performance, obtained a p-value of 0.000 with a T statistic of 6.735, which means that emotional intelligence has a positive and significant effect on performance. The effect of job satisfaction on performance, obtained a p-value of 0.021 with a T statistic of 2.039 which means job satisfaction has a positive and significant effect on performance. Conclusion: It can be concluded that emotional intelligence and job satisfaction affect the performance of nurses at the General Hospital Hermana Lembean.